Diversity of vascular plant species in the montane boreal forest of western Canada in response to climatic changes during the last 25 ka, fire, and land use - Harris, Stuart A. (ERDKUNDE, 2008)
This paper examines the biodiversity of vascular plants in the vast boreal forest area of the southern Cordillera of western Canada. It was glaciated until 11 ka, and since then, vascular plants have had difficulties colonizing the deglaciated areas from the surrounding refugia. Problems include the topography, the comparatively inhospitable climate, limited source areas, natural wildfires, and fluctuations in climate. As a result, the forest consists of up to 494 species of vascular plants at any one site compared to 871 species at Mount Rainier, Washington State. For comparison, 2,993 taxa have been reported from British Columbia indicating the limited colonization that has occurred. European Man has added to these problems by increasing fire frequency and by extensive, repeated logging of large areas. A limited amount of intensive irrigated agriculture also occurs near southern rivers and lakes. The end result is a limited range of species, of which 30% are regarded as rare or endangered. The consumers of the resulting biomass are therefore also limited in their food supply.